2020
DOI: 10.1111/1751-7915.13703
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐tuning ethanol oxidation pathway enzymes and cofactor PQQ coordinates the conflict between fitness and acetic acid production by Acetobacter pasteurianus

Abstract: Cofactor engineering is employed by manipulating ethanol respiration chain dehydrogenase module expression, cofactor PQQ biosynthesis module and various combinations of two modules to further improve acetic acid productivity.The synergistic regulation of alcohol/aldehyde dehydrogenase expression and cofactor PQQ level could not only efficiently relieve conflict between increased acetic acid production and compromised cell fitness, but also greatly enhance acetic acid tolerance of Acetobacter pasteurianus to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 54 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…According to Merli et al. (2021) , the growth of AAB typically decelerates at acetic acid concentrations above 40 g/L; however, certain strains, such as A. pasteurianus , exhibit resistance to these elevated concentrations, a tolerance essential for efficient ethanol oxidation ( Han et al., 2020 ; Gao et al., 2021 ). The present study used a high initial acetic acid concentration of 45 g/L, and the obtained acetification rate of 1.13 ± 0.05 g/L d corroborates the acidity resistance of A. pasteurianus ; this rate is comparable to values reported in similar studies ( Hidalgo et al., 2010 ; Qi et al., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to Merli et al. (2021) , the growth of AAB typically decelerates at acetic acid concentrations above 40 g/L; however, certain strains, such as A. pasteurianus , exhibit resistance to these elevated concentrations, a tolerance essential for efficient ethanol oxidation ( Han et al., 2020 ; Gao et al., 2021 ). The present study used a high initial acetic acid concentration of 45 g/L, and the obtained acetification rate of 1.13 ± 0.05 g/L d corroborates the acidity resistance of A. pasteurianus ; this rate is comparable to values reported in similar studies ( Hidalgo et al., 2010 ; Qi et al., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic flux analysis of the pathway from ethanol and glucose revealed that overproduction of the PQQ-dependent ADH is an effective way to improve the ethanol-oxidizing respiratory chain. pBBR1MCS-2 was used in A. pasteurianus to express genes of the membrane-bound alcohol dehydrogenase (adhA) and aldehyde dehydrogenase (aldH), PQQ biosynthesis genes (pqqAB or pqqABCDE), and combinations thereof, each under the control of the promoter P tuf that was 1.8-fold stronger than P adhA in GFP reporter assays (Gao et al 2020a). Synergistic expression of these genes could not only efficiently relieve the conflict between increased acetic acid production (69 g/L in semi-continuous cultivation) and compromised cell fitness, b ut al s o e nh an c ed th e a ce t i c a ci d t o l er an c e of A. pasteurianus to a high initial concentration of 3% (v/v) thereby shortening the duration of the starting-up process from 116 to 99 h. This strategy is of significance for decreasing costs for producing high-strength acetic acid industrially and will also be useful for the production of other desired organic acids, especially those involving PQQ-dependent enzymes.…”
Section: Other Expression Plasmids Used In Acetobactermentioning
confidence: 99%
“…Initially, ADH initiates the conversion of ethanol to acetaldehyde by removing hydrogen atoms, leading to the production of acetaldehyde and the reduction of NAD+ to NADH. Acting as a catalyst, ADH accelerates ethanol oxidation and facilitates NAD+ reduction (Gao et al, 2021 ; Zakhari, 2006 ). Subsequently, ALDH plays a crucial role by catalysing the further oxidation of acetaldehyde to acetic acid through hydrogen atom elimination (Miah et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%